2019
DOI: 10.1177/0011128719877347
|View full text |Cite
|
Sign up to set email alerts
|

Examining Prisoner Misconduct: A Multilevel Test Using Personal Characteristics, Prison Climate, and Prison Environment

Abstract: The aim of the current study was to examine if prisoner characteristics (personal characteristics and prison climate) and prison environment were related to prisoner misconduct, using data from a nationwide prospective cohort study examining the experience of prison climate in the Netherlands ( N = 4,427). The results indicated that both personal characteristics and certain (social) domains of prison climate, such as the quality of staff–prisoner relationships, were related to prisoner misconduct, as well as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 75 publications
(126 reference statements)
4
50
0
2
Order By: Relevance
“…It is therefore concluded that physical aggressive incidents are mainly related to atmosphere and repression. The association between repression and aggressive incidents in general (including physical aggressive incidents) is in line with the deprivation model which states that aggression is not so much caused by client characteristics but by environmental factors such as sociotherapists' behaviour (Bosma et al, 2019). However, the cause-effect relationship is still unclear, and the association between aggression and repression stresses the importance of awareness on processes in which these factors interact.…”
Section: Structural Equation Modellingsupporting
confidence: 74%
“…It is therefore concluded that physical aggressive incidents are mainly related to atmosphere and repression. The association between repression and aggressive incidents in general (including physical aggressive incidents) is in line with the deprivation model which states that aggression is not so much caused by client characteristics but by environmental factors such as sociotherapists' behaviour (Bosma et al, 2019). However, the cause-effect relationship is still unclear, and the association between aggression and repression stresses the importance of awareness on processes in which these factors interact.…”
Section: Structural Equation Modellingsupporting
confidence: 74%
“…While this research has played a key role in identifying potential risk factors for misconduct, the extent to which these factors are generalisable to other jurisdictions needs investigation, given the diversity that can exist between different countries, their cultures, prison populations, sentencing practices and prison conditions. Increasingly, studies are investigating the factors influencing misconduct in jurisdictions beyond North America (Beijersbergen et al, 2015;Bosma et al, 2020;Kuo, 2020;Reisig & Mesko, 2009). This paper adds to this growing scholarship and contributes to new knowledge in two ways.…”
mentioning
confidence: 88%
“…Prison misconduct can be assessed using official and self-report measures (Steiner & Wooldredge, 2014). Official measures assess how often someone has been found guilty of prison rule infraction through the prison disciplinary system, while self-report measures assess individuals' recollections of past involvement in misconduct (Bosma et al, 2020;Steiner & Wooldredge, 2014). Official measures may underestimate misconduct due to under-reporting and differences in recording and enforcement practices, while self-reporting may underestimate misconduct due to recollection or social desirability biases (Bosma et al, 2020;Bottoms, 1999;Steiner & Wooldredge, 2014).…”
Section: Risk Factors For Prison Misconductmentioning
confidence: 99%
“…Recurrent prisoners differ in their adjustment to confinement compared to first-time prisoners. For instance, whereas recurrent prisoners may demonstrate some positive adjustments such as greater psychological wellbeing and more participation in self-help programs (e.g., Souza and Dhami, 2010), they may also demonstrate some negative behaviors such as rule-breaking (e.g., Bosma et al, 2020). In the present study, people in lockdown were either more or equally compliant with the rules of lockdown as were first-time prisoners with the rules of prison, however, there may be less compliance during future lockdowns.…”
Section: Directions For Future Researchmentioning
confidence: 99%